Good tachyons, bad bradyons: Role reversal in Einstein-nonlinear-electrodynamics models - Marco A.A. de Paula; Haroldo C.D. Lima Junior; Pedro V.P. Cunha; Carlos A.R. Herdeiro; Luís C.B. Crispino (Physics Letters B)
In relativistic mechanics, the 4-velocity and the 4-momentum need not be parallel. This allows their norm to have a different sign. This possibility occurs in nonlinear electrodynamics (NED) models minimally coupled to Einstein's theory. Surprisingly, for a large class of NED models with a Maxwell limit, for weak fields, the causal (acausal) photons, as determined by their 4-velocity, have a spacelike (timelike) 4-momentum, leading to good tachyons and bad bradyons. Departing from weak fields, this possibility is determined solely by the concavity of the NED Lagrangian, which is consistent with the Dominant Energy Condition analysis. As a corollary, some popular regular black hole solutions sourced by NED, such as the Bardeen and Hayward solutions, are acausal.